Pengaruh Model Pembelajaran Team Games Tournament (TGT) Terhadap Prestasi Belajar Penjas Kelas VII di SMP Negeri 5 Karawang Barat - Endah Khairun Nissa; Evi Susianti; Ine Rahayu Purnamaningsih (Peneliti.net, 2022)
This study aims to determine the effect of the teams games tournaments (TGT) learning model on physical education learning achievement for class VII at SMP Negeri 5 Karawang Barat, this study uses an experimental method and uses a quantitative approach with a total sample of 80 students in class VII A and VII E in the activity. In learning, sampling is done using cluster random sampling, based on the results of data processing that has been analyzed, the answers to the hypotheses that have been previously proposed by the researcher have been obtained. The results and conclusions about the influence of the Teams Games Tournamens (TGT) learning model on physical education learning achievement for class VII at SMP Negeri 5 Karawang Barat. Has an influence on physical education learning achievement, especially on the material of physical fitness activities. This is proven by doing a study that was carried out when learning material for physical fitness activities. In the application of the Teams Games Tournamens (TGT) learning model on the material of physical fitness activities, there is a significant influence in the Teams Games Tournamens (TGT) learning model on physical education learning achievement, so that by using the Teams Games Tournamens (TGT) learning model, learning activities become more effective. fun and interesting, besides that the Teams Games Tournamens (TGT) learning model is very effective and efficient given to students in carrying out physical education learning activities at SMP Negeri 5 Karawang Barat.